Structure Determination, Conformational Flexibility, Internal Dynamics, and Chiral Analysis of Pulegone and Its Complex with Water. Issue 3 (6th December 2017) - Krin, Anna; Pérez, Cristóbal; Pinacho, Pablo; Quesada‐Moreno, María Mar; López‐González, Juan Jesús; Avilés‐Moreno, Juan Ramón; Blanco, Susana; López, Juan Carlos; Schnell, Melanie
Abstract: In the current work we present a detailed analysis of the chiral molecule pulegone, which is a constituent of essential oils, using broadband rotational spectroscopy. Two conformers are observed under the cold conditions of a molecular jet. We report an accurate experimentally determined structure for the lowest energy conformer. For both conformers, a characteristic splitting pattern is observed in the spectrum, resulting from the internal rotation of the two non‐equivalent methyl groups situated in the isopropylidene side chain. The determined energy barriers are 1.961911(46) kJ mol −1 and 6.3617(12) kJ mol −1 for one conformer, and 1.96094(74) kJ mol −1 and 6.705(44) kJ mol −1 for the other one. Moreover, a cluster of the lowest energy conformer with one water molecule is reported. The water molecule locks one of the methyl groups by means of a hydrogen bond and some secondary interactions, so that we only observe internal rotation splittings from the other methyl group with an internal rotation barrier of 2.01013(38) kJ mol −1 . Additionally, the chirality‐sensitive microwave three‐wave mixing technique is applied for the differentiation between the enantiomers, which can become of further use for the analysis of essential oils. Abstract : And yet it moves : Two conformers of pulegone and their internal dynamics, resulting from the two non‐equivalent methyl groups, were observed and analyzed using microwave spectroscopy in the gas phase. This leads to accurate experimental structures for the lowest energy conformer and its cluster with water. The internal rotation of one of the methyl groups is hindered upon complexation with water. Additionally, the microwave three‐wave mixing technique was applied for the differentiation between the enantiomers of pulegone.